Phenotypic and Genotypic Characteristics of a Tigecycline-Resistant Acinetobacter pittii Isolate Carrying blaNDM–1 and the Novel blaOXA Allelic Variant blaOXA–1045 - Ding, Zixuan; Li, Zhaoyinqian; Zhao, Yuanqing; Hao, Jingchen; Li, Tingting; Liu, Yao; Zeng, Zhangrui; Liu, Jinbo (Frontiers in Microbiology, 2022)
A tigecycline-resistant Acinetobacter pittii (TRAP) clinical strain from pleural fluid carrying a blaNDM-1 gene and a novel blaOXA gene blaOXA−1045 was isolated and characterized. The AP2044 strain acquired two copies of the blaNDM-1 gene and five antibiotic resistance genes (ARGs) from other pathogens. According to the whole-genome investigation, the GC ratios of ARGs (50–60%) were greater than those of the chromosomal backbone (39.46%), indicating that ARGs were horizontally transferred. OXA-1045 belonged to the OXA-213 subfamily and the amino acid sequence of OXA-1045 showed 89% similarity to the amino acid sequences of OXA-213. Then, blaOXA-1045 and blaOXA-213 were cloned and the minimum inhibitory concentrations (MICs) of β-lactams in the transformants were determined using the broth microdilution method. OXA-1045 was able to confer a reduced susceptibility to piperacillin and piperacillin-tazobactam compared to OXA-213. AP2044 strain exhibited low pathogenicity in Galleria mellonella infection models. The observation of condensed biofilm using the crystal violet staining method and scanning electron microscopy (SEM) suggested that the AP2044 strain was a weak biofilm producer. Quantitative reverse transcription-PCR (qRT-PCR) was used to detect the expression of resistance-nodulation-cell division (RND) efflux pump-related genes. The transcription level of adeB and adeJ genes increased significantly and was correlated with tigecycline resistance. Therefore, our genomic and phenotypic investigations revealed that the AP2044 strain had significant genome plasticity and natural transformation potential, and the emergence of antibiotic resistance in these unusual bacteria should be a concern for future investigations.